Does Consciousness Disappear in Dreamless Sleep?. Issue 12 (December 2016) - Windt, Jennifer M.; Nielsen, Tore; Thompson, Evan
Abstract : Consciousness is often said to disappear in deep, dreamless sleep. We argue that this assumption is oversimplified. Unless dreamless sleep is defined as unconscious from the outset there are good empirical and theoretical reasons for saying that a range of different types of sleep experience, some of which are distinct from dreaming, can occur in all stages of sleep. We introduce a novel taxonomy for describing different kinds of dreamless sleep experiences and suggest research methods for their investigation. Future studies should focus on three areas: memory consolidation, sleep disorders, and sleep state (mis)perception. Our proposal suggests new directions for sleep and dream science, as well as for the neuroscience of consciousness, and can also inform the diagnosis and treatment of sleep disorders. Trends: Dream science has mostly focused on REM sleep, but there is growing interest in serial awakening paradigms that collect reports from numerous awakenings throughout the night to contrast dreaming and dreamless sleep within the same sleep stage, including NREM sleep and SWS. Studies of spontaneous cognition, including mind wandering and dreaming, are leading to an increased focus on understanding both mental activity and neural dynamics as being largely 'intrinsic' or self-generated rather than 'extrinsic' or stimulus-driven. Although research on the neural correlates of consciousness has focused largely on the specific contents of consciousness, the investigation of global states of consciousness (such as sleep, dreaming, and wakefulness) and their relation to disorders of consciousness is receiving increasing attention.